Pengaruh Pengetahuan Akuntansi dalam Mengatur Gaya Hidup Mahasiswa Akuntansi Universitas Muhammadiyah Malang - Andini Nur Fadilah; Hari Setiono; Muhammad Bahril Ilmiddaviq (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Technological advances are a major factor in lifestyle changes that can encourage humans to always feel less satisfied with what they currently have, thus triggering sustainable consumption patterns of goods and services without deep consideration. In determining lifestyle, accounting plays an important role for a person because it helps him manage expenses to achieve the desired lifestyle. This study aims to examine the effect of accounting knowledge on lifestyle. The object of research focused on students of the accounting study program at Muhammadiyah University of Malang class of 2022 and 2023. The dependent variable used is lifestyle, while the independent variables used include learning in college, financial literacy, and financial management. Sample determination using probability sampling technique with disproportionate stratified random sampling method. Research data collection was carried out by distributing questionnaires to students. The results showed that, learning in college, financial literacy, and financial management both partially and simultaneously there was a positive and significant influence on the lifestyle of students of the accounting study program at Muhammadiyah University of Malang. In addition, the relationship between the two variables is very strong.